Sistema informático para la gestión de expedientes de la investigación formativa en la carrera de informática de la Espam MFL. - Fernández Lectong, Narcisa Mariana (2013)
This research aimed to optimize the management of research records in career training Informatics ESPAM MFL, through the creation of a computer system. For this purpose, the methodology XP (Xtreme Programing), also has a friendly interface and features a centralized database, all information handling itself, with great independence and security, as data that are stored are managed by a system database management Microsoft SQL Server professional. Also the whole system is done using Visual Studio.NET technology. With the implementation of the same, significantly reduces the time for recording and accessing data, resources and materials used for it (toner, paper, printers, copiers, time, etc). Enables eliminate double documentation, to be able to have it digitally at the time it is needed. On the other hand represents an efficient control mechanism by the Department to be able to check at any time from their computers the development of research in planning and implementation. In conclusion we can say that with this system you get all the advantages that brings true automation of information.